PENGARUH SIKAP MASYARAKAT TERHADAP KEBERADAAN LOKALISASI PROSTITUSI DOLLY DAN MARAKNYA PROSTITUSI ONLINE MELALUI JEJARING SOSIAL FACEBOOK SERTA IMPLIKASINYA PADA KETAHANAN SOSIAL BUDAYA (Studi Pada Masyarakat Kota Surabaya, Provinsi Jawa Timur) - Diana Agustianingsih (Jurnal Ketahanan Nasional, 2014)
There was positive and signifi cant effect of the community rejection attitude on the existence of Dolly prostitution localization and the rampant online prostitution on social network facebook with the high Surabaya social culture resilience. This purpose of this paper was discovering the community’s attitude on Dolly prostitution localization existence and on the rampant online prostitution on social network facebook in Surabaya and also discovering the effect of community’s attitude on Dolly prostitution localization existence and on the rampant online prostitution on social network facebook in Surabaya on Surabaya’s social culture resilience. The research was conducted with the survey method, the sampling was with questionnaire. The sampling technique was conducted with sampling proportional sampling at the 5 administrative regions in Surabaya. The research’s variable was the community. The collected data was measured with Likert scale. The result showed positive and significant effect of the community’s rejection on prostitution activities inside the Dolly prostitution localization complex and on social network facebook with the Surabaya high social culture resilience and therefore Surabaya community rejected the existence of Dolly prostitution in physic and on virtual world with online prostitution.Keywords: Effect, Community, Prostitution, Social Culture Resilience